Survey for Babesia spp. in wildlife in the eastern United States - Eliza Baker; Michelle Dennis; Alex Jensen; Kayla Buck Garrett; Christopher A. Cleveland; Michael J. Yabsley; Justin D. Brown; Kyle Van Why; Richard Gerhold (International Journal for Parasitology: Parasites and Wildlife)
Babesia is a diverse genus of piroplasms that parasitize the red blood cells of a wide variety of mammals and avian species, including humans. There is a lack of knowledge on the Babesia species of carnivores and mesomammals in the eastern United States and the potential impacts of these species on the health of humans and domestic animals. We surveyed 786 wild mammals in the eastern United States by testing blood, spleen, and heart samples with PCR targeting the 18S rRNA region of apicomplexan parasites. We also performed PCR targeting the cytochrome c oxidase subunit 1 (cox1) region of each unique clade identified with 18S rRNA sequencing. We found a high positivity of Babesia spp. infection in raccoons (Procyon lotor), foxes (Vulpes vulpes and Urocyon cinereoargenteus), and striped skunks (Mephitis mephitis), and low positivity in Virginia opossums (Didelphis virginiana). No Babesia infections were detected in coyotes (Canis latrans), black bears (Ursus americanus), groundhogs (Marmota monax), muskrats (Ondatra zibethicus), or mink (Neovison vison). Skunks carried a diverse number of strains including a potential novel species of Babesia related to B. gibsoni, a strain closely related to a B. microti-like species known to cause disease in river otters, as well as a separate B. microti-like strain. Raccoons primarily carried B. microti-like strains, though there was a high diversity of sequences including Babesia lotori, Babesia sensu stricto MA230, and Babesia sp. ‘Coco.’ Foxes exclusively carried B. vulpes. In addition to Babesia spp., a high positivity of Hepatozoon spp. infection was found in mink, while low positivity was found in raccoons and muskrats. Wildlife in the eastern United States carry a diverse range of Babesia species including several novel strains of unknown clinical significance.